Diversity and abundance of dipteran species at two different elevations in Gunung Datuk, Negeri Sembilan, Malaysia - Khairul Husna N.; Noor Nasuha A.A.; Saiyid Jalaluddin S.S.; Muhammad Luqman Hakim A.; Nurul Fatihah A.L.; Idris A.B.; Siti Khairiyah M.H. (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
A study on diversity and abundance of Diptera was conducted at two different elevations of Gunung Datuk viz. low (200 m) and high (700 m) from December 2014 to February 2015 using Malaise traps. Three malaise traps were set up in each elevation. A total of 1028 individuals of Diptera consisting of 31 families and 71 morphospecies were successfully collected. The abundance of Diptera at low elevation had the highest number of individuals collected with 627 (27 families, 62 morphospecies), while at high elevation only 401 individuals have been collected (23 families, 48 morphospecies). The most abundant family was Cecidomyiidae (322 individuals) while the least abundance was showed by the families Tipulidae, Rhagionidae and Agromyzidae with only one individual. The Shannon Weiner Diversity (H’) showed that low elevation had the higher diversity value with H’= 3.71. Further analysis conducted by using T-test showed that there was no significant difference between both elevations (P > 0.05). Overall, this study showed that the diversity and abundance of Diptera were higher at low elevation compared to high elevation.